Analisis Fundamental Makro, Struktur Modal, Struktur Kepemilikan Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Agri-Food Yang Terdaftar Di Bursa Efek Indonesia 2014-2023 - Ruri Istia Damayanti; Hwihanus Hwihanus (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This study aims to analyze the effect of macro fundamentals, capital structure, ownership structure on firm value with profitability as an intervening variable in agri-food companies listed on the Indonesia Stock Exchange from 2014 to 2023. This research uses documentation studies as a data collection technique and for data processing, Smart-PLS (Partiral Lerast Squarers) is used. The results show that capital structure has a significant influence on firm value, while ownership structure does not show a significant influence. In addition, profitability is proven to be an intervening variable that strengthens the relationship between capital structure and firm value, but does not strengthen the relationship between firm size and firm value. These findings provide important implications for the management of Agri-Food companies in making decisions related to financing and ownership strategies to increase firm value.